2023
DOI: 10.1111/ncn3.12765
|View full text |Cite
|
Sign up to set email alerts
|

Obesity prevalence factors associated with sympathetic overactivity and hypertension

Wahid Shah,
Imran Ali,
Waniya Shahid
et al.

Abstract: BackgroundObesity is the most significant worldwide public health problem and is integrally related to negative cardiovascular disease and hypertension results. The association between obesity and overweight elevated blood pressure is well known, and so it is calculated that 65%–78% of primary hypertension cases are accounted for by obesity.AimThis study aims to focus on whether obesity prevalence factors are associated with sympathetic overactivity and hypertension.MethodsThe pathways by which hypertension is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…According to the newest research, 34.8% of individuals were classified as overweight, while 14.1% were classified as obese in China. 30 Meanwhile, MetS, T2D, HUA, and hypertension 31 are common complications of obesity. Growing clinical evidence underscores high SUA levels were a potential predictor for a wide range of metabolic disorders, including T2D, 14 obesity, 32 metabolic syndrome, 19 and obesity-related fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…According to the newest research, 34.8% of individuals were classified as overweight, while 14.1% were classified as obese in China. 30 Meanwhile, MetS, T2D, HUA, and hypertension 31 are common complications of obesity. Growing clinical evidence underscores high SUA levels were a potential predictor for a wide range of metabolic disorders, including T2D, 14 obesity, 32 metabolic syndrome, 19 and obesity-related fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…30 Obesity is an important contributing factor in the incidence and development of hypertension. 31 A study has found that elevated SUA marks a pre-inflammatory state and impacts the role of HDL-c on carotid atherosclerosis. 32 The study has confirmed that people with low HDL are more than 4 times more likely to develop MetS than people with normal HDL, and people with a high UHR are 2.9 times more likely to have MetS.…”
mentioning
confidence: 99%